The Overview of the Electrical Fixing and Conservation (International Journal of Innovative Research in Engineering & Management, 2021)
Electrical maintenance is the process of keeping the electronics  equipment connected with panels, or in any other electrical  device. Electrical maintenance focuses on repairing, replacing  and maintaining electrical equipment utilized on a big scale.  Maintenance covers different tasks including testing, repairing  and replacing of the electrical and electronics equipment in  buildings controlled by industrial, corporate, private and government organizations. In this article talked about the  electrical installation and maintenance of power systems, in  which maintenance of transformer displayed and its reading  sample value of the equipments also presented. In this paper  research of maintenance and installation split into two sections  including rural and urban, it is observed that temperature,  weather and environment are different for various locations  which affect the equipment life and their and rate of  maintenance is varied with regard to place. The ability of  electrical repair is extremely essential since that expertise will  determine the life of equipment and plant. In this document also  displays the kinds of equipments needed during the  maintenance and installation. Maintenance and installation are  fascinating study subjects which are helpful for engineers,  every equipment and gadget requires maintenance thus in this  paper scope of maintenance given.
Keywords: Availability; Utilization; Maintenance; Installation; Facilities; Programmed